Odpowiedzi

2010-01-28T18:44:15+01:00
-3(5a-3b-4)=-15a+9b+12
6(-a+2b-7)-10=-6a+12b-42-10=6a+12b-52
4(a-b)-(-4a+2b)=4a-4b+4a-2b=8a-6b


3(x+2y)-4(2x+y)= 3x+6y-8x-4y=-5x+2y
-5*-2+2*0,5=10+1=11

naj???
2010-01-28T18:45:03+01:00
Zad1.
-3(5a-3b-4)= -15a + 9b + 12
6(-a+2b-7)-10= -6a +12b - 42
4(a-b)-(-4a+2b)= 4a - 4b + 4a - 2b = 8a - 6b
Zad2.
3(x+2y)-4(2x+y)= 3x + 6y - 8x -4y = -5x + 2y
-5x + 2y = -5 x -2 + 2 x ½ = 10 + 1 = 11
2010-01-28T18:45:08+01:00
1


-15a+9b+12
-6a+12b-42-10
4a-4b+4a+2b


2. -15